Overview of Sexuality Satisfaction in Breast Cancer Patients at RSUD Prof. Dr. Margono Soekarjo Purwokerto - Rahma Melinda; Adiratna Sekar Siwi; Ikit Netra Wirakhmi (LPPM Universitas Harapan Bangsa, 2024)
Cancer is the cause of death and loss of hope for cancer patients around the world, especially breast cancer. Breast cancer sufferers have psychological, social, and physical effects. One of the physical effects is decreased sexual function. Sexual function in cancer patients is an important element that can affect their quality of life. One of the causes of decreased quality of life in cancer is influenced by sexual function. The purpose of this study was to find out the description of sexual satisfaction in breast cancer patients at RSUD, Prof. Dr. Margono Soekarjo Purwokerto. This type of research is quantitative, using descriptive research methods with a cross-sectional approach. The sampling technique using non-probability sampling with purposive sampling using the Slovin formula obtained the results of 79 respondents. The research instrument used was the Sexual Satisfaction Scale for Women (SSS-W) questionnaire, which consisted of 30 questions. Data analysis using a univariate test. Data collection was carried out on April 5–18, 2023. The results showed sexual satisfaction in breast cancer patients at RSUD, Prof. Dr. Margono Soekarjo Purwokerto, namely in the satisfied category, 56 respondents (70,9%)